Association between long-term exposure to PM2.5 and thyroid nodules in school-aged children and adolescents: a cross-sectional study in Eastern China - Mao Liu; Pei-hua Wang; Yun-jie Ye; Li Shang; Yu-ting Xia; Yang Wang; Zhen Ding; Yan Xu (Environmental Health)
Abstract Background Long-term exposure to particulate matter with aerodynamic diameter ≤ 2.5 μm (PM2.5) are linked to thyroid nodules in adults, but epidemiological evidence in children and adolescents and adjustments for key confounders are lacking. This study aimed to explore the association between long-term exposure to PM2.5 and the prevalence of thyroid nodules in school-aged children and adolescents. Methods A cross-sectional study including 10,739 primary and junior high school students was conducted in Jiangsu Province, China, in 2021. Annual PM2.5 concentrations were estimated by a satellite based space-time model based on machine learning. Individual exposure concentrations were assigned according to the school addresses of the participants. High-resolution diagnostic ultrasound imaging was used to detect the thyroid nodules. After adjustment for covariates, the link between the two-year (2019–2020) average PM2.5 concentrations and thyroid nodules was estimated using a generalized linear mixed-effects model. The concentration-response (C-R) curves were smoothed using a restricted cubic spline function. Stratified analyses were performed to evaluate the modification effects of covariates on associations. Results The average age of the 10,067 participants (51.9% boys) was 11 years, with a thyroid nodule prevalence of 30.5%. A non-linear positive correlation was found between the increase in prevalence of thyroid nodules and two-year average exposure concentration of PM2.5. The C-R relationship curve between thyroid nodules and PM2.5 had a J-shaped structure with a threshold value of 39.7 µg/m3. Following covariates adjustment, the odds ratio (OR) and 95% confidence interval (CI) linked to thyroid nodules were 1.515 (1.199, 1.915) for per standard deviation (SD) increase in two-year average PM2.5 concentrations (> 39.7 µg/m3). The sex-specific associations found among adults were not observed in our stratified analyses. Conclusions Our findings demonstrated that long-term exposure to PM2.5 was associated with a higher prevalence of thyroid nodules in children and adolescents. Strategies that consistently reduce PM2.5 pollution levels to ease the burden of non-communicable diseases have important public health implications.